Knowledge Management in Nepal’s Political Transformation: Enhancing Governance, Transparency, and Democratic Engagement through KM Practices in Major Political Parties - Gautam, Tara Prasad; Adhikari, Babu Ram; Lingden, Binod (GS WOW: Wisdom of Worthy Research Journal, 2024)
This paper explores the implementation and challenges of Knowledge Management (KM) practices within Nepali political organizations, specifically focusing on two prominent parties: the Communist Party of Nepal (Unified Marxist-Leninist) (CPN-UML) and the Nepali Congress (NC). The research employs a comparative case study approach to investigate how these parties manage knowledge creation, documentation, retention, and dissemination. It assesses their strategies for maintaining institutional memory, enhancing governance, and facilitating leadership transitions. The study reveals that CPN-UML prioritizes ideological training and structured political research, while NC emphasizes preserving historical records and leadership mentorship. Despite these efforts, both parties encounter significant obstacles, including hierarchical barriers, technological limitations, and fragmented knowledge systems that impede effective KM implementation. The paper concludes that adopting a more strategic, technology-driven KM framework could substantially enhance the adaptability, governance, and sustainability of political organizations in Nepal. This study provides valuable insights into the impact of KM on political party efficiency and resilience, offering actionable recommendations for improving KM practices in Nepali political entities.